LEARNING FROM HOME: SCHOOL AND PARENTS COLLABORATION IN MI MA'ARIF DARUSSALAM PRAMBANAN, YOGYAKARTA - Rina Rahmi; Ismuhul Fadhil (Universitas Pendidikan Indonesia, 2022)
The application of online learning during the covid-19 pandemic requires parents to be involved in the learning process. Learning will not be carried out effectively and efficiently if parents do not contribute to the learning objectives that have been set. This study aims to obtain information about the form of collaboration between parents and teachers carried out during online learning. The research method used is qualitative with a descriptive approach where the data source consists of primary and secondary data. The data collection techniques in this study used observation, interviews, and documentation. Meanwhile, the data analysis technique was processed through three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the form of collaboration between parents and the school was by forming an organization chaired by one of the guardians of the students named Paguyuban. This organizational structure was formed to facilitate communication and collaboration between schools and parents. In addition, the purpose of the organization is also as a forum for discussion of policies that will be implemented by the school based on the decision of the Head of School. As for the form of collaboration between parents and the school, parents act as providers of facilities, educators, and supervisors during the implementation of online learning. It is hoped that the collaboration between parents and the school will not only last during the implementation of online learning, but can be sustainable with or without the pandemic that is sweeping the world today so that innovative, collaborative, effective, and efficient education can be realized.